“The Song I am Singing”:: Gregory Scofield’s Interweavings of Métis, Gay and Jewish Selfhoods - Scudeler, Jane (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
While Gregory Scofield’s early works dealt largely with his Cree Métis ancestry and his sexuality, his vision now includes the recent discovery of his Jewish roots. Sensitive to the traditions and histories of his multiple heritages, he has carefully woven his disparate identities together by writing to “be himself.” In collections such as The Gathering: Stones from the Medicine Wheel, Love Medicine and One Song, Native Canadiana, and Thunder Through my Veins: Memories of a Métis Childhood, Scofield creates a multidimensional self-portrait that challenges society’s overly simplistic conceptions of the minority personality. He is, as Qwi-Li Driskill explains, a writer “who gives us back our tongues, who dislodges out silences and turns them into sites of resistances.”